Adaptation of General Phubbing Scale to Turkish Culture and Investigation of Phubbing Levels of University Students in Terms of Various Variables - Yam, F.C.; Kumcaǧiz, H. (AVES, 2020)
This study aimed to adapt the Generic Phubbing Scale (GPS) to Turkish culture and to examine the phub-bing levels of university students concerning various variables. Acceptable goodness-of-fit indices were found in the first-order confirmatory factor analysis (x2/df=2.47, GFI=0.92, IFI=0.92, CFI=0.95, NFI=0.92 AGFI=0.89, TLI=0.94, and RMSEA=0.067) and the second-order confirmatory factor analysis (x2/df=2.61, GFI=0.92, IFI=0.95, CFI=0.95, NFI=0.92 AGFI=0.89, TLI=0.93, and RMSEA=0.070) performed to test the construct validity of the GPS. Later, the significance of the upper and lower 27% groups was analyzed using an independent t-test. The analysis results showed that the scale has the power to measure the desired characteristics. Chronbach’s alpha internal consistency coeﬃcient was found to be a=89. The study examined university students’ phubbing levels in terms of various variables and performed a hierarchical regression analysis to explore whether the variables of smartphone addiction, fear of missing out, and boredom proneness were predictive variables for university students’ phubbing addiction levels. According to the results, these three variables were found to be significant predictor variables for the phubbing levels of university students. © by 2020 Turkish Green Crescent Society.
Keywords: Addiction; Phubbing; Reliability; Scale; Validity